Ambient Noise Characterization of Shallow Water Environment - Santoso, Tri Budi (Politeknik Elektronika Negeri Surabaya (PENS), 2015)
Understanding of environmental characteristic is a key factor in design of communication system. This paper describes an ambientÂ noise characterization of measurement in the shallow water ofSurabaya bay. The result showed that probability density function (pdf) of ambient noise is close to a Gaussian distribution with the mean of -2.85x10-5 and deviation standard of 9.87x10-4. Validation has been done by using mean square error (MSE) and Bhattacharya distance. Fitting between cdf of measurement result and theory was done by using MSE with the value of and Kolmogorov Smirnov test with the value of 3.9x10-4 and 4.9x10-2 respectively. In the frequency domain analysis, it is showed that in the range of 0 9 kHz has a deceasing level from -100 until -140 dB. In the frequency of 9 13.5 kHz, the spectral is flat as like a white. It can be used as a reference in decision of range frequency of underwater acoustic communication systems that will be applied.Keywords: ambient noise, statistical characteristics, underwater acoustic.